Role of transition metals present in air particulate matter on lung oxygen metabolism. (December 2016) - Magnani, Natalia D.; Marchini, Timoteo; Garcés, Mariana; Mebert, Andrea; Cáceres, Lourdes; Diaz, Luis; Desimone, Martín; Evelson, Pablo A.
Abstract: Several epidemiological studies have shown a positive correlation between daily increases in airborne particulate matter (PM) concentration and the occurrence of respiratory and cardiovascular diseases. Transition metals present in air PM were associated with adverse health effects after PM exposure. The aim of this work was to study lung O2 metabolism after an acute exposure to transition metal-coated nanoparticles (NPs). Female Swiss mice (25 g) were intranasally instilled with a suspension of silica NP containing Ni (II), Cd (II), Fe (III), or Cr (VI) at 0, 0.01, 0.05, 0.1, and 1.0 mg metal/kg body weight. Lung O2 consumption was found to be significantly increased after the exposure to most doses of Ni-NP and Fe-NP, and the 0.05 mg metal/kg body weight dose of Cr-NP, while no changes were observed for Cd-NP. Lucigenin chemiluminescence (as an indicator of NADPH oxidase (NOX) activity) was evaluated in lung homogenates. Only Ni-NP and Fe-NP have shown the ability to induce a significant increase in lucigenin chemiluminescence. In order to establish the possible occurrence of pulmonary oxidative stress, TBARS levels and the GSH/GSSG ratio were determined. The higher doses of Ni-NP and Fe-NP were able to induce an oxidative stress condition, as shown by changes in both TBARS levels and the GSH/GSSG ratio. Taken together, the present results show differential effects for all the metals tested. These findings emphasize the importance of transition metals present air PM in PM adverse health effects, and contribute to the understanding of the pathological mechanisms triggered by the exposure to environmental PM.